Copper nanowires embedded in boron nitride nanosheet-polymer composites with enhanced thermal conductivities for thermal management. (8th May 2020) - Yin, Chuan-Gen; Liu, Zhong-Jie; Mo, Rui; Fan, Jin-Chen; Shi, Peng-Hui; Xu, Qun-Jie; Min, Yu-Lin
Abstract: With the rapid development of modern microelectronic devices, high-performance thermal interface polymer materials are of ever-rising importance. However, polymers commonly have very low intrinsic thermal conductivities, thence, introducing the thermal conductive nanofillers was considered to be one of the efficiently ways to enhance the thermal conductivity. The construction of effective thermal conductive pathway is essential for the thermal conductivity of polymer-based composites. In this context, toward the common functionalized boron nitride nanosheet (f-BNNS)/polymer composites, we found that the introduction of a very low amount of one-dimensional (1D) copper nanowires (CuNWs) can bring significantly further improvement in thermal conductivity. The in-plane thermal conductivity of f-BNNS-CuNWs/poly (vinyl alcohol) (PVA) composite film with 0.1 wt% of CuNWs can achieved at 6.5 W/(mK) which is 1.76 times as high as that of f-BNNS/PVA composite film at the same filling content of f-BNNS. The use of high-aspect-ratio CuNWs is beneficial to the formation of random bridges or networks with conductive f-BNNS and facilitates the phonon transfer leading to high thermal conductivity. SEM images demonstrated that the adjacent 2D f-BNNS plates were in tandem with 1D CuNWs. The obtained results offer a facile and feasible way to design and fabricate the highly thermal-conductive polymer composites as advanced thermal interface polymer composite materials. Graphical abstract: Image 1 Highlights: f-BNNS and CuNWs were introduced into the PVA matrix together. A continuous heat conductive network of CuNWs and f-BNNS was formed. There are strong interface interactions between f-BNNS and CuNWs. A low content of CuNWs brings great improvement on thermal conductivity.